(3ef GdebGdI GdChdi ef cJGH JOHjQ GdeJhMOs - (3GHf HGLI , CHh HcQ Hf GdUGFZ GdSQbSWj,J (B533 (3g` s
(3ChdgG (B:s
(3bGd CHh HcQ GHf GdUGjZ daXI GdJOHjQ JbGd Ydi JQSH CaYGd fMh ZGjI ebUhOg hdgPG jWdbhf Ydi GdEdg eOHQ GdYGde hgPG bO jchf HGdbhI s
(3BNQgG (B:s
(3ajchf Hg SQeOjkG hjchf ajg eYfi jTHg GdcGjfg GdaGSOI ajchf Hg cGFfkG aGSOkG aGdEfSGf ef CYGLjH GdWHjYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B63s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs